2020
DOI: 10.7759/cureus.8549
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Features and Survival Outcomes of Signet Ring Cell Carcinoma of the Appendix: An Analysis of the Surveillance, Epidemiology, and End Results Database

Abstract: Background and objective Signet ring cell carcinoma of the appendix (SRCCA) is an exceedingly rare tumor, and very limited data are available regarding its characteristics and survival probabilities. Our objective in this study was to utilize the Surveillance, Epidemiology, and End Results (SEER) database to explore the patient and tumor characteristics and to characterize the three-and five-year cancer-specific survival (CSS) probabilities of SRCCA. Methods Patients with SRCCA diagnosed between 2000 and 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…We found that over one-half cases presented with metastatic disease, and SC had almost twice the odds of metastasis at diagnosis than CA. Studies have reported the five-year cancer-specific survival of metastatic appendiceal GC to be 4-7%, and a median survival of only 19 months, in contrast to 60 months for nonmetastatic disease [ 4 , 14 ]. Our study found the median survival of metastatic disease to be similar at 20 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that over one-half cases presented with metastatic disease, and SC had almost twice the odds of metastasis at diagnosis than CA. Studies have reported the five-year cancer-specific survival of metastatic appendiceal GC to be 4-7%, and a median survival of only 19 months, in contrast to 60 months for nonmetastatic disease [ 4 , 14 ]. Our study found the median survival of metastatic disease to be similar at 20 months.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of metastases greatly influences the clinical course of patients with appendiceal carcinoma. Metastatic disease confers poor prognosis and entails difficult treatments [2][3][4][5]. Due to the rarity of appendiceal carcinoma, epidemiological data on metastatic disease at presentation is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to mucinous adenocarcinoma, SRCC-A may have distant metastases at diagnosis, and 64% of patients have lymph node metastasis, which is significantly higher than that of other histological types. [1,2] Zheng et al confirmed that SRCC-A is a distant tumor, accounting for 66.5% of the total cases. [8] Ovary and peritoneum are common sites of metastasis, and Kulkarni et al concentrated on the ovarian implantation metastasis and extensive peritoneum metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumors of the appendix represent approximately 0.4% of all gastrointestinal tract tumors, and are mainly found in about 1% of appendectomies. [1] The most frequent location of tumors with the signet ring cell pattern is the stomach (96%), followed by the colon, rectum, gallbladder, and pancreas. Signet-ring cell carcinoma (SRCC), which is an infrequent type of colorectal cancer, accounts for 0.5% to 2.6% of all adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, la efectividad de estos regímenes de quimioterapia sigue siendo controvertida (1,17) . El papel de la quimioterapia no está claramente establecido, aunque los casos con enfermedad estadio IV pueden ser tratados con quimioterapia adyuvante basada en 5-fluorouracilo, en forma similar a los adenocarcinomas colorrectales (18,19) . La paciente del presente caso fue sometida a quimioterapia con resultados favorables.…”
Section: Discussionunclassified